2017
DOI: 10.12688/f1000research.9652.2
|View full text |Cite
|
Sign up to set email alerts
|

Mursamacin: a novel class of antibiotics from soil-dwelling roundworms of Central Kenya that inhibits methicillin-resistant Staphylococcus aureus

Abstract: Antibiotic-resistant bacteria, also called "superbugs", can at worst retrogress modern medicine to an era where even sore throats resulted in death. A solution is the development of novel types of antibiotics from untapped natural sources. Yet, no new class of antibiotic has been developed in clinical medicine in the last 30 years. Here, bacteria from insect-killing Steinernema roundworms found in the soils of Central Kenya were isolated and subjected to specific molecular identification. These were then assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…BMMCB and XN45 were both described as X. griffiniae species [20, 32]. We previously demonstrated XN45 and X.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…BMMCB and XN45 were both described as X. griffiniae species [20, 32]. We previously demonstrated XN45 and X.…”
Section: Resultsmentioning
confidence: 99%
“…These were above the same species thresholds of 98.65, 97 and 97 % respectively [11, 50]. Conversely, strains BMMCB and XN45 were not conspecific, as demonstrated by their respective percentage nucleotide similarities values of 98.545, 93.67 and 92.066 % for 16S rRNA, recA and serC genes respectively [20]. Indeed, BMMCB was not an X.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…strain BMMCB was described as an Xenorhabdus. griffiniae species ( Mothupi et al, 2015 ), but we ( Awori et al, 2017 ) demonstrated that its nucleotide identities values for the recombinase A ( recA ), phosphoserine transferase ( serC ), and small subunit ribosomal ribonucleic acid (rRNA) (SSU) genes, with those of the type species, were below the accepted threshold for conspecific strains—97% for protein-coding genes ( Tailliez et al, 2010 ) and 98.7% for SSU gene ( Kim et al, 2014 ).…”
Section: Xenorhabdus and Photorhabdus Bac...mentioning
confidence: 93%